Letter: severe COVID‐19 infection and biologic therapies—a cohort study of 7 808 patients in France. Issue 7 (9th September 2020) - Bataille, Pauline; Amiot, Aurélien; Claudepierre, Pascal; Paris, Nicolas; Neuraz, Antoine; Lerner, Ivan; Garcelon, Nicolas; Rance, Bastien; Grisel, Olivier; Moreau, Thomas; Bernaux, Melodie; Audureau, Etienne; et al.
Abstract : LINKED CONTENT This article is linked to Taxonera et al and Taxonera & Alba papers. To view these articles, visit https://doi.org/10.1111/apt.15804 and https://doi.org/10.1111/apt.16055